2018
DOI: 10.1016/j.appet.2017.11.089
|View full text |Cite
|
Sign up to set email alerts
|

The impact of price and nutrition labelling on sugary drink purchases: Results from an experimental marketplace study

Abstract: Increasing price was associated with reduced sugary drink purchases. Enhanced FOP labelling results highlight the need for further research to investigate their potential impact. The study adds empirical support for taxation to reduce sugary drink consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 31 publications
2
68
0
4
Order By: Relevance
“…Nutrient warnings reduced participants' choice of snacks and drinks high in critical nutrients [74,76], the level of critical nutrients in beverages and snacks purchased [70], or improved the overall nutritional profile of purchases [61] compared to a no-label control or to other labeling types. However, in another study of purchases, there was no statistically significant effect of warning labels, but there was a trend for nutrient warning labels to reduce purchases of sugary drinks [63].…”
Section: Egnell Et Al 2019 [80]mentioning
confidence: 93%
See 1 more Smart Citation
“…Nutrient warnings reduced participants' choice of snacks and drinks high in critical nutrients [74,76], the level of critical nutrients in beverages and snacks purchased [70], or improved the overall nutritional profile of purchases [61] compared to a no-label control or to other labeling types. However, in another study of purchases, there was no statistically significant effect of warning labels, but there was a trend for nutrient warning labels to reduce purchases of sugary drinks [63].…”
Section: Egnell Et Al 2019 [80]mentioning
confidence: 93%
“…Acton and Hammond, 2018 [63] Behavior: There was no statistically significant effect of labeling, though there was a trend for the "high sugar" nutrient warnings to reduce the likelihood to purchase a sugary drink and encourage participants to purchase drinks with less sugar. Table 3.…”
Section: Neal Et Al 2017 [61]mentioning
confidence: 99%
“…While the vast majority of FOPL systems present an interpretive (e.g., France’s Nutri-score [ 16 ], Australia’s Health Star Rating [ 17 ]) or nutrient-specific (e.g., Food Industry’s Guideline daily amounts [ 18 ], the UK’s color-coded GDA [ 19 ]) nutrient profile of the relative healthiness of foods [ 20 , 21 ], a new paradigm for FOPL, known as nutritional warnings, have been designed to help people limit their intake of foods that contain high amounts of critical nutrients of public health concern (i.e., sodium, sugars, and saturated fat). Recent research has shown that a “High in” nutrient based FOPL is an effective consumer tool for providing more accessible and comprehensible nutrition information to consumers [ 22 ], helping them to limit nutrients of concern [ 23 ] and also enhancing perceptions of control over the healthiness of their food decisions [ 24 ]. In 2016, Chile became the first country to implement mandatory “high in” FOPL designed to help people limit their intake of foods that contain high amounts of critical nutrients of public health concern (i.e., sodium, sugars, and saturated fat) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, evidence from experimental studies, qualitative investigations and real-world evaluations suggests that nutrient-specific FOP warnings can be easier to understand (2,4) , effective at reducing consumer preference and purchase intention (2,(4)(5)(6)(7)(8)(9)(10)(11)(12) , and can affect actual purchasing and consumption of targeted foods (13)(14)(15) . Research from various countries also shows strong consumer support for the labelling systems (15)(16)(17)(18) .…”
mentioning
confidence: 99%